Paku Kawat Lycopodiella cernua (L.) Pic. Serm. (Lycopdiaceae-Lycopodiales) dari Provinsi Riau – Kajian Morfologi dan Sekuen DNA berdasarkan Primer RBCL - Nery Sofiyanti; Mayta Novaliza Isda (Jurnal Biologi Universitas Andalas, 2019)
Moss club (Lycopodiella cernua) is one of fern members distributed in Riau Province. The aimed of this study were to characterized the morphological characters and to analized its DNA sequence based on rbcl primer. Samples were collected from the field, documented and characterized the morphological charaters. DNA were isolated and amplified using PCR method and rbcl primer.  DNA sequnces were then analized using BLAST   Lycopodiella cernua collected from Riau Province was characterized by having creeping and erect rhizome that covered by microphyl, and terminal strobili. Rbcl fragmen of Lycopodiella cernua was sucssesfully amplified with 643 bp length. BLAST result confirmed the  rbcl fragmen of this club moss.